Genome‐wide profiling and identification of insulin signaling pathway genes of subterranean termite castes. Issue 9 (8th July 2021) - Haroon; Li, Yu‐Xin; Ye, Chen‐Xu; Ma, Xiao‐Qin; Su, Jian; Su, Xiao‐Hong; Xing, Lian‐Xi
Abstract: Aging and longevity is a dynamic, chronological process assumed to originate from several hallmarks causing archetypal and beguiling cycles with incredible natural diversity. This phenomenon is widely observed in different animals, and the estimated age of Drosophila melanogaster, Caenorhabditis elegans, Daphnia longispina are a few days to weeks. Reproductive termites live for 30 years, although the root cause of longevity in termite castes is still debated for molecular and cellular changes. Insulin and insulin signaling pathway‐related (IIS) genes are important metabolic factors (glucose) highly conserved in lower to higher organisms. Therefore, in this study, we pooled Reticulitermes chinensis castes as primary king (PK), primary queen (PQ), ergatoid king "SWRK" and queen "SWRQ", male (WM), and female (WF) workers. We determined transcriptome sequencing of R. chinensis castes as a model organism for longevity to investigate the insulin signaling pathway and longevity genes. Through RNA‐sequencing, we identified 35 IIS‐pathway‐related genes out of 343 to the KEGG pathway in ergatoid king and queen, PK, PQ, WM, and WF. Among these genes, Tsc2, akt2‐a, mTOR, EIF4E, Pdk1, and RPS expressed highly in ergatoid king and queen, PK, and PQ. However, a significant cornerstone tradeoff between reproductive and non‐reproductive efforts for early life is essential for evolutionary longevity. The present study concludes that a highly conserved IIS‐pathway is evidence for the prolonged termite reproductive life span. We recommended devoting insulin signaling pathway genes to their biological function for termite survival and new insights into the maintenance and relationships between biomolecular homeostasis and remarkable longevity.